Investigating Secondary School Pre-service Teachers’ Perspectives on Utilizing ICT in Teaching English Language Skills - Deyura, Gean; Hanifa, Rizaldy (Universitas Negeri Padang, 2025)
The integration of Information and Communication Technology (ICT) in English Language Teaching (ELT) has significantly influenced how English is taught and learned, particularly in the context of teaching the four main skills: listening, speaking, reading, and writing. In modernization initiatives, pre-service teachers are increasingly expected to incorporate ICT into their practicum teaching. This study aims to explore the perspectives of secondary school pre-service English teachers regarding the use of ICT in teaching English language skills. This research used a qualitative descriptive method and the data were collected through semi-structured interviews involving pre-service teachers from Universitas Negeri Padang who completed their teaching practicum in secondary schools. The research focused on the utilization of ICT tools that they implemented. Especially about the management, application, and impression of ICT in teaching English language skills based on their experience. The findings indicated that while most participants acknowledge the pedagogical value of ICT in increasing student engagement and improving lesson delivery, they also face challenges and issues while using ICT in teaching process. Furthermore, pre-service teachers exhibit a positive attitude toward ICT but require more institutional support to optimize its integration. These insights can help teacher training institutions enhance their programs and better prepare future educators for technology-driven classrooms.